Prevalência e variação da contagem de ovos em escolares infectados com Schistosoma mansoni e geohelmintoses em áreas de baixa e moderada endemicidade no Brasil - Federico, Andréa L’Amour (2019)
Schistosomiasis, caused by trematoda of the genus Schistosoma, is a neglected tropical disease. Brazil, where it is caused by Schistosoma mansoni, has the largest endemic area in the Americas, and it is estimated that 42.9 million people live in areas at risk of infection and 6.8 million are infected. The objective of this study was to evaluate the prevalence and intensity of infection of schistosomiasis mansoni and geohelminths diagnosed through Kato-Katz in areas of low and moderate endemicity in Brazil. This is a longitudinal study and for 3 consecutive days, 1 sample / day of faeces (2 slides per sample) was collected from 6 to 20 year-old schoolchildren for the Kato-Katz diagnosis in 542 children in the municipality of Malhador / Sergipe and 572 children in Januária / Minas Gerais. As a result, 24.35% (n = 132) positive cases were found for schistosomiasis in the municipality of Malhador and 5.28% (n = 30) in Januária. In the municipality of Malhador / SE, the community with the highest number of infected was Tabua, with 53.77% (n = 57), in Januária / MG, the community of São Joaquim was 13.11% (n = 16).The community of Tabua / SE presented a higher prevalence of infection in the range among schoolchildren aged 16-20 years, however, in Januária there was no significant relationship between the age group and community. Other parasitic infections such as Ascaris lumbricoides (0.55%) and Trichuris trichiura (3.32%) were found in Malhador / SE. After the treatment, only five schoolchildren from the municipality of Malhador / SE, were still infected. According to the results, it can be concluded that the regions studied present low and moderate endemicity and a variation of the intensity of infection among the communities, showing that these areas are conducive to the spread of the disease.